SYSTEMIC EFFECTS RELATED TO THE USE OF 1% CYCLOPENTOLATE HYDROCHLORIDE EYE DROPS IN REFRACTOMETRY IN CATS - da Silveira, Camila P.B. [UNESP]; Piso, Dunia Y.T.; Barros Sobrinho, Alexandre A.F. [UNESP]; Crivelaro, Roberta M. [UNESP]; Abreu, Thais G.M. [UNESP]; Filezio, Marcella R. [UNESP]; Aldrovani, Marcela [UNESP]; Laus, José L. [UNESP] (De Gruyter, 2024)
In veterinary medicine, 1% Cyclopentolate hydrochloride (CP) has emerged as an intermediate-term cycloplegic and mydriatic agent. This study evaluated the pupillary dilation time and systemic effects related to the use of 1% CP eye drops in cats. Fifteen cats, aged 1 to 6 years and weighing 2.5 to 7 kg, were included in the study. After receiving written consent from the owners, each cat was administered two drops of 1% Cyclopentolate, 10 minutes apart, into both eyes. Data on pupil dilation, systemic symptoms, and behavioral changes were collected and analyzed using frequency and descriptive statistics. Pupillary dilation was observed 30 minutes after administering the second drop of 1% CP. The duration of pupillary dilation was 36 hours for 26.6% of the eyes, 48 hours for 53.4%, and 60 hours for 20%. Within the first hour after medication administration, seven cats exhibited episodes of salivation and vomiting, and four displayed behavioral changes, including aggressiveness and increased vocalization. Results suggest that 1% CP eye drops cause mydriasis for at least 36 hours and can lead to temporary adverse effects on the gastrointestinal and nervous systems.
Keywords: cyclopentolate; cycloplegic; feline; mydriatic; toxicity